(untitled) (International Journal of Medical and Surgical Sciences, 2019)
In restorative dentistry, the use of composite resins with direct technique for the replacement of missing tooth structure is very common. One drawback is that surface roughness allows the adherence of microorganisms and the formation of dental plaque, being the polishing technique a key stage in the restoration process. The aim of this paper is to review the process of bacterial colonization of composite resins used with direct technique. According to in vitro studies, bacterial adhesion on microhybrid composite resins is 3.91 ± 0.52 UFC and on nanohybrid is 3.34 ± 0.74 UFC. Resins with particle size of 2.5 micrometers contained a greater volume of biofilms and enabled adhesion of S. mutans; in turn, resins with particle size of 0.1 to 0.4 micrometers showed lower bacterial adherence. As summary, the degree of bacterial colonization depends on hygiene, polishing technique and composition of restorative material: the bigger the particle size, the greater the adhesion of bacterial plaque.